(untitled) (Conferencea, 2023)
Today, confessional education and enlightenment is developing in new socio-cultural, political and economic conditions. The problems of spiritual and moral education have become one of the leading places in the public consciousness of Uzbekistan. The increase in the number of believers, the opening of many religious educational institutions, the revival of the centuries-old religious and cultural traditions among the Russian people, first of all, implies the training of highly qualified personnel.